The Effect of Parasocial Interaction and Influencer Credibility on Purchase Intention - Rahmawati, Cintami Indah; Puspaningrum, Astrid (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
Beauty industry, especially perfumery, keeps innovating to compete in the technological advancement era. One of the innovation is marketing the products digitally using social media, and this can boost purchase intention. Social media marketing exploits parasocial interactions and influencer credibility. The objective of this research is to identify the effects of parasocial interaction and influencer credibility on the intention to purchase the products of HMNS, a local perfume brand via TikTok in Malang City. This explanatory research elucidates the positions of its examined variables and the effects of a variable to another. Using non-probability sampling method and purposive sampling technique, 140 people of Malang City with the minimum age of 17 years who have watched the TikTok contents of influencers regarding HMNS at least twice were selected as the respondents. The data was harvested from Liker-scaled questionnaires and was analyzed using multiple linear regression in the Statistical Package for Social Sciences (SPSS) version 26. This study finds that parasocial interaction and influencer credibility positively and significantly affect the purchase intention.